Analisis Kebutuhan Media Video Animasi dengan Bantuan Aplikasi Canva pada Pembelajaran Sejarah - Arlita, Zahra; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This study aims to explore knowledge related to the need for developing animated video media assisted by the Canva application, which is intended to enhance students’ causal thinking skills in history learning. The approach used in this research is a qualitative method with descriptive data. The data collection techniques employed include observation, interviews, and pre-tests. Through these three techniques, the researcher was able to comprehensively identify the needs for developing animated video media. The findings reveal two main focuses: student analysis and curriculum analysis. From the student analysis, it was found that students require learning media that can foster the development of causal thinking skills. This need arises due to the limited ability of teachers to create instructional media, particularly technology-based media. Meanwhile, based on the curriculum analysis, it was found that history learning at Grade XI, Phase F, refers to the Merdeka Curriculum, with the core material focusing on the Proclamation of Indonesian Independence. The learning achievement expected from this material is for students to be able to explain causal relationships and the sequence of events surrounding the Proclamation of Independence.